Screen-Printing and 3D-Printing Technologies in Electrochemical (Bio)sensors: Opportunities, Advantages and Limitations - Panagiota M. Kalligosfyri; Antonella Miglione; Stefano Cinti (ECS Sensors Plus)
Electrochemical sensors and biosensors play pivotal roles for detecting target analytes in clinical pharmaceutical, environmental and agri-food monitoring. Although screen-printing represents an affordable and versatile approach to produce wide examples of devices, 3D-printing technique is emerging as a strong alternative in sensor manufacturing. Both approaches present significant opportunities for advancing sensor design, but each has distinct advantages and limitations that influence application suitability. This perspective article examines the experimental differences between screen- and 3D- printing for fabricating portable electrochemical devices. We discuss their opportunities, advantages and limitations across diverse fields, highlighting the experimental features depending on the analytical requirements.